Effectiveness of an intervention to improve the vaccination coverage against Streptococcus pneumoniae in patients with chronic kidney disease - Ignacio Hernández-García; Carlos Aibar-Remón (Human Vaccines & Immunotherapeutics, 2021)
Pneumococcal vaccination is recommended for chronic kidney disease (CKD) patients. We evaluated the impact of implementing a hospital vaccine consultation on their vaccination coverages. A sample was drawn from consecutive cases referred to our clinic between November 2014 and June 2018. 101 patients were analyzed: 4 had received the pneumococcal conjugated vaccine 13-valent at the time of the first appointment, whereas 93 had received it after being seen (RR (95%-CI) = 23.3 (8.88–60.85)). Moreover, 5 had received the pneumococcal polysaccharide vaccine 23-valent at the time of the first appointment, whereas 90 had received it after being seen (RR (95%-CI) = 18.0 (7.64–42.42)). Implementing a hospital-based vaccine consultation represents an effective intervention to improve pneumococcal vaccination coverage in these patients.